Clinical and socio-demographic determinants of pentazocine misuse among patients with sickle cell disease, Benin City, Nigeria: a case-control study - Adewoyin, Ademola (Pan Afr Med J, 2019)
INTRODUCTION: Opioids are a mainstay in sickle cell disease (SCD) pain care. Opioids are known to cause physical and/or psychological dependence. Increasingly, a significant number of Nigerian SCD patients ("Pentaholics") are observed to abuse pentazocine. This trend is associated with new patterns of medical complications. This study aimed to describe the local spectrum of pentazocine abuse complications and identify possible clinical and socio-demographic determinants. METHODS: We conducted a case control (age matched) study involving 50 booked SCD patients (25 cases and 25 controls) receiving care at the University of Benin Teaching Hospital, Benin City, Nigeria. Relevant clinical and socio-demographic details were collected and analyzed. Associations of categorical variables were tested using chi square or Fishers exact test. RESULTS: The median participants’ age and duration of pentazocine abuse/self-use were 32 and 7 years respectively. Pentazocine injections were gotten from local pharmacies and patent medicine stores without any need for physician prescriptions (84% of cases). The buttocks, the thigh and the upper arm/deltoid were the commonest site of injection. Major complications observed were chronic ulcers on the thigh, deep wounds with abscess, healed scar at multiple sites, lower limb swelling and venous thrombosis. Working in healthcare fields/hospitals (Doctor, Nurses, Pharmacists) was significantly associated with pentazocine abuse. CONCLUSION: Health personnel or hospital workers living with SCD are more likely to abuse pentazocine. There is need for prompt triage and optimal control of acute sickle pain, institutional protocols for pain management and strict regulations on supply of prescription drugs such as pentazocine.